Analisis Kebutuhan Modal Kerja Kontraktor Berdasarkan Sistem Pembayaran di Gedung Rawat Inap Rumah Sakit Sanjiwani Gianyar - Made Sudiarsa; I Ketut Sutapa (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
A construction project is a series that is only implemented once and is generally short-term, with limited resources. Before the implementation of a construction project runs, it usually starts with the preparation of a work plan and a project implementation time (time schedule). The realization of work plans in the field often experiences delays in the process, because revenue realization is very much determined by the selection of the payment system used by the contractor which will affect the project cash flow (cash flow), the amount of working capital required, the progress of a job, and to determine policy alternatives. that needs to be done so that the project does not experience a deficit. This study aims to determine the payment system that requires less working capital and benefits the contractor in terms of project benefits. The analysis uses 2 alternative policies carried out by the contractor during the project, alternative 1 by making a loan to the bank and alternative 2 with a material payment policy. From the results of this research analysis, it is found that the MC payment system does not require working capital because the project cash flow condition is always a surplus, while the term payment system requires working capital in the form of a bank loan of IDR 410,000,000.00 so that the project cash flow condition does not experience a deficit, as was done. on policy alternatives 1.